Desarrollo de una metodología para el entendimiento del comportamiento de las propiedades de crudos atmosféricos tipoparafínicos y asfalténicos, para su aplicación en el modelamiento de fluidos a través de ecuaciones de estado en la cuenca del Valle Medio del Magdalena (2020)
This research project focuses on the determination of two differentiated fluid trains along the Middle Magdalena Valley Basin, according to the belief developed by the directors assigned by the company Ecopetrol SA, which were determined through the creation and implementation of a comparison methodology that would clarify and visualize in a clearer and more concise way the correlation that the properties typically measured have in a crude characterization analysis carried out on the different fields located in the geographical area of interest. Firstly, an organization of the data was carried out, which was used as an input for the development of the research, proceeding to differentiate those properties for which more information was available, such as: API gravity, sulfur content, SARA analysis, number acid, metal content, viscosities, among others; to subsequently perform a statistical analysis to determine the reliability and degree of dispersion of the data and thus determine whether said information could be used in the comparison process; After this, the type of crude produced by each field in the basin was classified according to the available information.